Penerapan Cahaya Monokromatik untuk Perbaikan Kuantitas Telur Puyuh (Coturnix coturnix japonica.L) - Kasiati, Kasiyati; Kusumorini, Nastiti; Maheshwari, Hera; Manalu, Wasmen (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
The quail’s egg have value of nutrient which similar to the chicken’s egg and the duck’s egg. Various of the programme of the light to improve repair of the quantity and the quality of the quail egg. The objectives of this research were to applied monochromatic light to repair the quality and quantity of the quail egg. Two hundred and seventy female quails (DOQ) were divided into nine treatments of light, with ten replications and three quails in each replication, the treatments were without light, controls with 15 and 25 W, red, green, and blue lights with intensities of 15 and 25 lux. Control treatment used incandescent bulb. The red, green, and blue lights were provided by light emitting diodes (LED). All lights treatment were given for 14 h daily, started from 17.00 to 07.00. Parameters measured were amount of the egg weekly, henday egg production, and quality of the egg consist of the weights of the egg, protein and fat of the egg. The result showed that quails exposed to blue light had higher of the amount of the egg, henday production, and the weights of the egg, while the quality of the egg, such as protein and fat in the egg were not change (P>0,05). Blue light could be used to improve repairing quantities of the quail egg.